KETIDAK SELARASAN ATURAN PEMBERIAN WILAYAH IZIN USAHA PERTAMBANGAN KHUSUS TERHADAP BADAN USAHA MILIK ORGANISASI KEMASYARAKATAN KEAGAMAAN: Inconsistencies in the Regulation of Special Mining Business Permit Allocation to Business Entities Owned by Religious Community Organizations - Simangunsong, Anggiat Binsar Simangunsong (Jurnal Globalisasi Hukum., 2025)
In the history of mining management in Indonesia, the government first opened the opportunity by granting Special Mining Business License Areas (WIUPK) to business entities owned by religious mass organizations. This article's study shows that there is no regulation in  Law Number 3 of 2020 concerning the amendment to Law Number 4 of 2009 on Mineral and Coal Mining (“Law Number 3 of 2020”) and the Omnibus Law Number 11 of 2020 (“Job Creation Law”) regarding the granting of WIUPK to Business Entities Owned by Religious Mass Organizations (Business Entities of Religious Organizations). However, Government Regulation Number 25 of 2024 (GR Number 25 of 2024), which amends Government Regulation Number 96 of 2021 concerning the implementation of coal mining activities, provides for the granting of WIUPK to Religious Mass Organizations. This government policy raises serious questions regarding the inconsistency between the laws and the implementation of WIUPK granting to business entities of religious organizations, as well as the legal basis for granting WIUPK to religious mass organizations, especially since, in the legal hierarchy, such provisions are not aligned. This misalignment may lead to negative implications in the implementation of the regulation and set a poor precedent for the granting of WIUPK for both mineral and coal commodities. This study also employs normative legal methodology using two approaches: the conceptual approach and the statute approach. Therefore, it is important to ensure consistency across all levels of regulation, from the highest-ranking laws to the implementing regulations, so that legal enforcement can be carried out effectively.